2020
DOI: 10.1055/s-0040-1702967
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Reflux Symptom Index and the Endolaryngeal Findings Scale after Treatment in Individuals with Laryngopharyngeal Reflux

Abstract: Introduction Laryngopharyngeal reflux (LPR) is a prevalent condition in outpatients visiting the otorhinolaryngological clinic, with many controversies regarding its diagnosis and follow-up. Therefore, there is a need for clinical instruments that can diagnose individuals and monitor the results of their treatment. Objective To evaluate the applicability of the scores translated and adapted to Brazilian Portuguese: Reflux Symptom Index (RSI) and Endolaryngeal Reflux Findings Scale (ERFS), as instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
5
7
0
Order By: Relevance
“…Another study conducted by Lee et al Also stated a significant change in the RSI score after receiving PPI therapy for four weeks, from 13.15 with a standard deviation of 8.68 to 10.03 with a standard deviation of 8.97 (p. <0.01) Lee et al (2014). It is also in line with a study conducted by Silva et al, which showed a significant decrease in the RSI score after PPI administration, from the mean initial score before treatment of 16.0 to 10.5 after being given therapy (p <0.001) Álvaro Siqueira Silva et al (2021).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Another study conducted by Lee et al Also stated a significant change in the RSI score after receiving PPI therapy for four weeks, from 13.15 with a standard deviation of 8.68 to 10.03 with a standard deviation of 8.97 (p. <0.01) Lee et al (2014). It is also in line with a study conducted by Silva et al, which showed a significant decrease in the RSI score after PPI administration, from the mean initial score before treatment of 16.0 to 10.5 after being given therapy (p <0.001) Álvaro Siqueira Silva et al (2021).…”
Section: Resultssupporting
confidence: 87%
“…It is consistent with Somashekara & Kamath's research in 2015, which showed that LPR incidence was more common in women (56.66%) than men (43.33%) Somashekara and Kamath (2015). Other studies also show that LPR is dominated by women, namely 85.7%, while men are only 14.3% Álvaro Siqueira Silva et al (2021). Another research conducted at RSUP DR. M. Djamil Padang for the period 2017 showed that LPR patients were found in 66.27% women and only 33.73% in men with a ratio of male to female ratio of 1: 2 Sa&apos;an and N (2017).…”
Section: Resultsmentioning
confidence: 89%
“…The RFS and RSI showed significant improvement after initiation of treatment at the 4th week and 12th week, respectively, and the p-value was found to be significant (< 0.01). The study results were found comparable with Belafsky et al [9][10] and Silva et al [12]. Belafsky continued treatment for a period of six months, whereas, in our study, treatment was given for three months.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found the mean age of patients who were diagnosed with LPR was 41.8 (SD=±10.1) years, which was comparable with studies in the published literature [ 12 ]. While most of the patients were female, i.e.…”
Section: Discussionsupporting
confidence: 88%
“…Another study conducted by Silva et al found a higher average age in LPR patients, which was 47.2 years, from the age of 29 years to 73 years. All of these studies shown that the average age of LPR patients globally is above 40 years [12], [13].…”
Section: Discussionmentioning
confidence: 99%